Machine learning techniques combined with dose profiles indicate radiation response biomarkers - Papież, Anna; Badie, Christophe; Polanska, Joanna (Zielona Góra: Uniwersytet Zielonogórski)
The focus of this research is to combine statistical and machine learning tools in application to a high-throughput biological data set on ionizing radiation response. The analyzed data consist of two gene expression sets obtained in studies of radiosensitive and radioresistant breast cancer patients undergoing radiotherapy. The data sets were similar in principle; however, the treatment dose differed.
Keywords: machine learning; gene profiling; radiation response; multiple random validation; transcription